Ancaman Perdamaian di Venezuela Akibat Kemerosotan Demokrasi Pada Masa Pemerintahan Nicolas Maduro - Maulidya, Al Dina (Parahyangan Center for International Studies, 2024)
This paper aims to describe the threat to peace in Venezuela, which occurred during the reign of Nicolas Maduro. The urgency of this research is the deterioration of democracy that occurred in Venezuela after Chavez left. Maduro is the president who was elected to replace Chavez in 2013. Political and economic instability, as well as the decline of democracy, have posed a threat to peace in Venezuela. This research is a descriptivequalitative study, with data using a library study. The Kantian triangle, which is part of Immanuel Kant's democratic peace theory, will be an analytical tool in this research. The Kantian Triangle determines three factors to achieve peace in democracy, namely: (1) democracy, (2) the existence of dependence between countries, and (3) state interactions in the international arena. The result of this research shows that Venezuela is not able to fulfill the three existing factors. First, the erosion of democratic values in the country. Second, dependence on other countries is difficult to materialize. This is because Maduro's policies are detrimental to investors, and the many humanitarian issues in Venezuela. The bad image of Maduro's government makes it difficult to maintain good relations with other countries. Third, although active in the United Nations, Venezuela continues to carry out the rules and principles of the organization. The failure to fulfill the three factors in the Kantian Triangle can pose a threat to peace in Venezuela. Keywords: Threat of Peace, Democratic Deterioration, Nicolas Maduro, Venezuela.